The macroeconomics of HIV/AIDS - Haacker, Markus (International Monetary Fund, 2004)
This paper analyzes the macroeconomics of HIV/AIDS. The paper highlights that the mortality and morbidity associated with AIDS make it unlike most other types of sickness and disease. The paper describes the most common approaches used in accounting for growth in the context of an HIV/AIDS epidemic. The impact of HIV/AIDS on education and the accumulation of human capital is discussed. The paper also discusses the impact of HIV/AIDS on the public sector, and elaborates certain demographic events specific to the HIV/AIDS pandemic
Keywords: Botswana